Analysis of English Syntactic Figures (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article analyses English and Uzbek are languages belonging to different families and different languages. According to the genealogical classification, the English language belongs to the Indo-European family, and part of this family belongs to the Germanic language family. The Uzbek language belongs to the Ural-Altaic family, and a part of this family belongs to the Turkic language family.. It also deals with analysis of syntactic figures in the English language, types of syntactic figures and their analysis. The importance of understanding types and ways of correct connecting words in English syntax.